Exploring the Design Space for Adaptive Graphical User Interfaces - Gajos, Krzysztof; Czerwinski, Mary; Tan, Desney; Weld, Daniel (Advanced Visual Interfaces 2006, 2006)
For decades, researchers have presented different adaptive user interfaces and discussed the pros and cons of adaptation on task performance and satisfaction. Little research, however, has been directed at isolating and understanding those aspects of adaptive interfaces which make some of them successful and others not. We have designed and implemented three adaptive graphical interfaces and evaluated them in two experiments along with a nonadaptive baseline. In this paper we synthesize our results with previous work and discuss how different design choices and interactions affect the success of adaptive graphical user interfaces.